Production of ACP fresh fruits and vegetables for export to the EEC - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Production de fruits et légumes frais dans les pays ACP pour l'exportation vers les pays de la CEE